Kongsberg Vision Meeting Abstracts 2021 - Baraas, Rigmor C (Scandinavian Journal of Optometry and Visual Science, 2021)
Kongsberg Vision Meeting was held at the University of South-Eastern Norway in Kongsberg, for the 13th time, on November 16–18, 2021. The meeting was organised as a three-day meeting with a clinical day, a research day and a lighting design day. Rigmor C. Baraas, Eilin Lundanes, Ann Elisabeth Ystenæs, Ellen Svarverud, Klaus Sjøhaug and Are Røysamb organised the three-day meeting. The theme this year was Speciality Contact Lenses and Architectural Lighting Design. Keynote speakers for the clinical optometry day and the research day were Eef van Der Worp, Nicola Logan, Fabrizio Zeri and Daddi Fadel. The keynote speakers for the lighting day were Sylvia Pont and Manuel Spitschan. The abstracts from invited and contributed talks on the different days are presented in the order they were given.